Evaluation of the combined effects of dimethoate and spirodiclofen on plants and earthworms in a designed microcosm experiment - Santos, Miguel J.G.; Ferreira, Vera; Soares, Amadeu M.V.M.; Loureiro, Susana (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2011)
► STEM showed to be a potential predictive tool in assessing pesticide mixtures. ► At field application rates the pesticides did not affect B.rapa and E.andrei. ► The binary mixtures had an antagonistic effect on B.rapa. ► In earthworms, synergism occurred at 10 times the field dose of both pesticides Most studies in soil ecotoxicology are designed to assess the effects of individual chemicals on individual test species, using a reference soil (e.g. LUFA 2.2, OECD soil). There is therefore an urgent need for a more comprehensive and integrated approach in order to assess the impact of chemical pollutants on soil ecosystems. In this study, a more realistic scenario in ecotoxicity evaluation was achieved through the use of microcosm-based experiments, using a small-scale terrestrial ecosystem (“STEM”) containing Mediterranean agricultural soil. Earthworms ( Eisenia andrei) and turnip seeds ( Brassica rapa) were introduced into the microcosms, in order to examine the effects of the acaricide spirodiclofen and the insecticide dimethoate, both in single and binary combination exposures. Results showed that for plants and earthworms the recommended application dose of both pesticides did not cause impairment of growth, although increasing concentrations resulted in a biomass decrease for both species. Earthworms were found to alter their depth distribution as a response to the combined application of the two pesticides, with this parameter being more sensitive than body mass. The various binary mixtures tested resulted in antagonistic effects on B. rapa shoot length and fresh weight. Regarding the depth distribution of earthworms, antagonism was observed at field dose, as well as at five times the field dose for both pesticides, while synergism occurred at ten times the field dose.